2003
DOI: 10.1182/blood-2002-10-3048
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of OX40 (CD134) regulates graft-versus-host disease (GVHD) and graft rejection in allogeneic bone marrow transplant recipients

Abstract: OX40 (CD134) is expressed on activated T cells; its ligand, OX40 ligand (OX40L) isexpressed on dendritic cells, B cells, and activated endothelial cells. To determine how OX40-OX40L interaction affects graftversus-host disease (GVHD), we used antagonistic anti-OX40L monoclonal antibody (mAb) or OX40 ؊/؊ donor or OX40L ؊/؊ recipient mice. Similar degrees of GVHD reduction were observed with each approach. Despite the fact that OX40 is up-regulated on both CD4 ؉ and CD8 ؉ T cells isolated during GVHD, the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 46 publications
4
70
1
1
Order By: Relevance
“…In summary, our results clearly demonstrate that gut-specific fast homeostatic proliferation plays a critical role in inducing guthoming a 4 b 7 + IL-17A + T cells, which is dependent on OX40 signals. Although the systemic inhibition of OX40 signals, either in OX40L-knockout mice or by treatment with an anti-OX40L mAb, drastically ameliorates several types of IBDs and GVHD (34,35,61), our study revealed that the OX40-OX40L interactions necessary for generating intestinal Th17 cells may occur in the MLNs. Therefore, it may be possible to develop therapeutic strategies for IBDs and GVHD by controlling the OX40-OX40L interactions in MLNs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, our results clearly demonstrate that gut-specific fast homeostatic proliferation plays a critical role in inducing guthoming a 4 b 7 + IL-17A + T cells, which is dependent on OX40 signals. Although the systemic inhibition of OX40 signals, either in OX40L-knockout mice or by treatment with an anti-OX40L mAb, drastically ameliorates several types of IBDs and GVHD (34,35,61), our study revealed that the OX40-OX40L interactions necessary for generating intestinal Th17 cells may occur in the MLNs. Therefore, it may be possible to develop therapeutic strategies for IBDs and GVHD by controlling the OX40-OX40L interactions in MLNs.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, both commensal bacteria and OX40 are required for fast proliferation in MLNs and for guttropic T cell accumulation in the lamina propria of the intestine. Studies in several animal models have demonstrated that OX40-OX40L interactions mediate the development of IBDs and GVHD, both of which are pathogenically associated with the homeostatic proliferation of CD4 + T N cells (34,35,61). Therefore, it is likely that a 4 b 7 + Th17 cells generated through fast homeostatic proliferation in MLNs are also involved in the pathogenesis of these diseases in an OX40-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…35 A second signal through T-cell co-stimulatory molecules and their ligands on APCs is required to achieve T-cell activation, proliferation, differentiation and survival. 36,37 An in vivo blockade of positive co-stimulatory molecules (CD28, ICOS, CD40, CD30, 4-1BB and OX40-those that activate T-cell response) reduces acute GVHD, [38][39][40][41][42][43] whereas a blockade of inhibitory signals (those that inhibit or exhaust T-cell response), such as programmed death-1 (PD-1) and CTLA-4, exacerbates acute GVHD in murine models. 44 Interactions that enhance or inhibit the function of APCs.…”
Section: Sensors Of Gvhdmentioning
confidence: 99%
“…Costimulatory pathways are now known to deliver both positive and negative signals and molecules from two major families, the B7 family and the TNF receptor (TNFR) family play pivotal roles in GVHD (97). Interruption of the second signal by blockade of various positive co-stimulatory molecules (CD28, ICOS, CD40, CD30, 4-1BB and OX40) reduces acute GVHD in several murine models while antagonism of the inhibitory signals (PD-1 and CTLA-4) exacerbates the severity of acute GVHD (2,(98)(99)(100)(101)(102)(103). The various T cell and APC costimulatory molecules and the impact on acute GVHD are summarized in Table 2.…”
Section: B Phase 2: Donor-t-cell Activation Differentiation and Migmentioning
confidence: 99%